Optically binary liquid crystalline blue phases induced by one-armed cholesterol-linked azobenzene molecules1. Issue 30 (14th August 2015) - Yin, Leicheng; Wu, Yeping; Gao, Jiangang; Ma, Jiajun; Hu, Zhijia; Zou, Gang; Zhang, Qijin
<x xml:space="preserve">Abstract</x> Optically binary liquid crystalline blue phases resulting from different isomerization degrees of the azobenzene molecules.